Website Manajemen Pemesanan dan Transaksi Barang Pada Perdagangan Besi Beton PT. Elang Perkasa Menggunakan Framework Laravel - Hartarto Junaedi; Eric Sugiharto Honggara; Felia Gabriella (KALBISCIENTIA Jurnal Sains dan Teknologi, 2023)
This research explains how to create and design a website application for order management and goods transactions at “PT. Elang Perkasa” reinforcing bar trading using the Laravel framework. The purpose of this research is to facilitate the recording of order and transaction data, find out the total load weight in each sales transaction, and make it easier for buyers to find out the latest information about their purchases. The research method used is Waterfall, where each stage is done sequentially and moves to the next stage when the previous stage has been completed. Therefore, the Waterfall method is recursive where each stage can be repeated continuously until it is perfect. This application can be used properly, can help users in knowing and managing information, and can reduce the occurrence of human error due to company employee errors.